THE PRISON HOUSES OF KNOWLEDGE: ACTIVIST SCHOLARSHIP AND REVOLUTION IN THE ERA OF "GLOBALIZATION" - D’Souza, Radha (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2009)
ABSTRACT. The rise of new social movements has produced an emerging discourse on activist scholarship. There is considerable ambiguity about what the term means. In this article I draw on my work as a trade unionist, political activist, and activist lawyer in Mumbai, and later as a social justice activist in New Zealand to reflect on the meaning of activist scholarship, interrogate the institutional contexts for knowledge, and the relationship of knowledge to emancipatory structural social transformations. Although based on personal experiences, this article provides a theoretically oriented meta-analysis of activist scholarship. LES PRISONS DE LA CONNAISSANCE : L’ACTIVISME ÉTUDIANT ET LA RÉVOLUTION À L’ÉRÈ DE LA « GLOBALISATION » RÉSUMÉ. La montée des nouveaux mouvements sociaux a provoqué l’émergence d’un discours novateur sur l’activisme étudiant. Il persiste cependant une grande ambiguïté quand à la signification de ce terme. Dans cet article, je m’inspire de mes travaux comme militante syndicale, activiste politique et avocate engagée à Mumbai, ainsi que de mon expérience en tant que activiste en justice sociale en Nouvelle-Zélande pour réfléchir sur le sens à donner à l’activisme étudiant, m’interroger sur les contextes institutionnels du savoir, et sur la relation existant entre le savoir et les transformations structurelles d’émancipation. Bien que prenant appui sur mes expériences personnelles, cet article étaye une méta-analyse théorique de l’activisme étudiant.